Knowledge and Role of Paediatricians/Paediatric Residents in Infant Oral Healthcare and Dental Home across Saudi Arabia: A Cross-Sectional Study - Satish Vishwanathaiah; Prabhadevi C. Maganur; Dhalia Hassan Albar; Ranya Hassan Albar; Mohammed Abdurabu Jafer; Safeyah A. Baeshen; Imtinan Ahmed Madkhali; Enas Jaber Mohana; Jawaher Saleh Sahli; Alhanouf K. Alnajdi; Manal Kinani Tahhah; Varsha Manoharan (MDPI AG, 2023)
The prevention of oral diseases in children is highly achievable through providing early exposure to oral healthcare habits, which would make children more receptive towards dental services. A cross-sectional study used a structured, self-explanatory questionnaire to evaluate the knowledge and role of 190 paediatricians and paediatric residents towards infant oral healthcare and the dental home across Saudi Arabia. The authors sent a link to the questionnaire, comprising 36 questions, by email, as a Google e-form. The response rate obtained was 87.36%. A major proportion (95.8%) of the respondents considered that paediatricians play an important role in promoting oral health. Around 45.8% of the practitioners recommended tooth brushing after the eruption of the first tooth. About 38% of the practitioners were unaware of the children's first dental visit. The majority (95.2%) agreed that there should be an increased awareness regarding home dental habits. Most of them (78.3%) examined the oral cavity for dental problems as a part of routine childcare, and the majority (75.3%) admitted that they did not evaluate fluoride needs. A statistically significant higher mean knowledge score was observed for practitioners with more than 30 years of experience (9.35 ± 2.29), and there was a significant positive correlation (r = 0.486) between the knowledge score and mean score for the role of paediatric practitioners. Overall, the study concluded that the knowledge of paediatricians and paediatric residents in SA towards infant oral healthcare and the dental home was inadequate, and their role in maintaining oral health was found to be moderately satisfactory.